2002
DOI: 10.1086/339401
|View full text |Cite
|
Sign up to set email alerts
|

Distant Cluster Hunting. II. A Comparison of X‐Ray and Optical Cluster Detection Techniques and Catalogs from theROSATOptical X‐Ray Survey

Abstract: We present and analyze the optical and X-ray catalogs of moderateredshift cluster candidates from the ROSAT Optical X-ray Survey, or ROXS. The survey covers the sky area contained in the fields of view of 23 deep archival ROSAT PSPC pointings, 4.8 square degrees. The crosscorrelated cluster catalogs were constructed by comparing two independent catalogs extracted from the optical and X-ray bandpasses, using a matched-filter technique for the optical data and a wavelet technique for the X-ray data. We cross-ide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 54 publications
8
75
3
Order By: Relevance
“…Moreover, using the RASS-SDSS galaxy cluster catalogue, Popesso et al (2004) show that a distinct class of "X-ray underluminous Abell clusters" does exist, with an X-ray luminosity L X that is one order of magnitude fainter than that expected for their mass according to the typical L X -mass relation (Popesso et al 2007a). This supports the concern of Donahue et al (2002) about the possible existence of biases in catalogues selected in different wavebands.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, using the RASS-SDSS galaxy cluster catalogue, Popesso et al (2004) show that a distinct class of "X-ray underluminous Abell clusters" does exist, with an X-ray luminosity L X that is one order of magnitude fainter than that expected for their mass according to the typical L X -mass relation (Popesso et al 2007a). This supports the concern of Donahue et al (2002) about the possible existence of biases in catalogues selected in different wavebands.…”
Section: Introductionsupporting
confidence: 79%
“…For example, it was shown by the first joint X-ray/optical survey (Donahue et al 2002) that only ∼20% of optically selected clusters appeared to be identifiable in X-rays, while ∼60% of the X-ray clusters were included in the optical sample. Understanding the possible selection effects hidden behind the different survey strategies is crucial to explain the small size of the overlap between the two different cluster catalogues (see for example Ledlow et al 2003;Gilbank et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Vikhlinin et al (1998), on whose 160d ROSAT catalogue the 400d sample builds (cf. Burenin et al 2007) detect four clusters in the field: VMF 189 (A 2246), VMF 190 (CL 1701+6414), VMF 191,and VMF 192. In an independent ROSAT analysis, Donahue et al (2002) detect these same four clusters plus RX J1702+6407, which we do not detect in WL. The redshift of z = 0.7 found for the Donahue et al (2002) optical counterpart of CL 1701+6414 deviates from the redshift of z = 0.45 measured by Burenin et al (2007) and all other references.…”
Section: Appendix A: Photometric Calibration Detailscontrasting
confidence: 43%
“…From its application to the SDSS, they produced a "CE cluster catalog" that included different galaxy density profiles, luminosity functions, and clusters dominated by either spirals or faint ellipticals. Additionally, Donahue et al (2002) have suggested that the CRS could be characteristic of massive clusters only (e.g., Aguerri et al 2007;Ascaso et al 2012). …”
Section: Introductionmentioning
confidence: 99%